Media pendidikan agama Islam berbasis Android: kelas X MA Al Islamiyah Kotabumi - Heri Cahyono; Adriyanto Adriyanto; Siti Atini; Junani Junani (Curricula: Journal of Curriculum Development, 2026)
Islamic Religious Education (Pendidikan Agama Islam or PAI) at the Madrasah Aliyah level currently faces challenges, including conventional teaching methods that are less appealing to the digital generation, which in turn leads to low student motivation and learning outcomes. This research aims to develop and test the feasibility, practicality, and effectiveness of Android-based learning media specifically designed for tenth-grade students. The method employed in this research is a research and development approach based on the Borg and Gall model, modified into several main stages. Data were collected through expert validation, user-response questionnaires, and learning-outcome tests to assess differences in student understanding. The research results revealed that this learning medium received a high feasibility rating from both material and media experts. Responses from students and teachers also indicated that this application is highly practical and easy to use in both independent learning and classroom settings. The use of digital media in PAI learning can enhance conceptual understanding and active student participation. This Android-based learning medium is a suitable, innovative solution, aligned with the characteristics of today's students, for creating a more interactive and enjoyable learning environment.